REVIEW LAND AND BUILDING TAX FOR THE PURPOSE OF LOCAL GOVERNMENT REVENUE INCREASE: THE CASE STUDY IN BANTUL REGENCY - , Sugiasih, Ir. Suryanto, MSP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia is a country which consists of many islands having different potencies, cultures and economic situations, so new legislations, which transferred part of central governmentâs authorities and revenue sources to local governments, were introduced in 1999. Thus, local governments enable to design and decide their own local policies which could be tailored and responsive to their special regional needs and situations. In order to achieve further fiscal decentralization, it is discussed and proposed how to increase local governmentâs revenue by focusing on the Land and Building Tax. Having increased Land and Building Tax is not only will increase government`s revenue, but also will encourage owner`s land to maximize land utilization. In order to examine the existing financial problems of local governments, the Bantul Regency, which is one of the typical regencies where urbanization has recently started, is chosen as the model regency for this research. This study is a qualitative research involving procedures, such as collecting data, analyzing data and interpreting findings. The data are NJOP data, land price data based on the notary reports, and land price data based on the interview. In general, data analysis was done by comparing between NJOP and land price in three regions: region that is affected by urbanization, region that is slightly affected by urbanization, and region that is not affected by urbanization. The result showed that the difference of NJOP and land price in the first region compared the second region and third region is large enough. In the first region, the average gap between NJOP and land price is Rp420.000,00, while in the second region and in the third region reach only Rp120.000,00 and Rp21.000,00. Even though there is a large gap between NJOP and land prices in the three regions, percentage of NJOP to land price in every region is not much different, ranging from 45 % - 60 %. There are four ways to be considered to increase the revenue of Land and Building Tax. Firstly, a local government can simply increase the tax rate of the Land and Building Tax. Secondly, an introduction of different tax rates of the Land and Building Tax, depending on the usage of land can be considered. Thirdly, in order to decrease any gap between NJOP and real market price of lands, regular revaluation of land value for NJOP can be more frequently conducted. Lastly, in order to mitigate the problem of the expensive costs of revaluation of land prices, an introduction of an automatic increase of NJOP in parallel either with a general inflation rate, an average increase of housing price or sales price of the property could be considered.